Use and Outcome of Remdesivir in patients with COVID 19 presenting to Mayo Hospital Lahore - Hina Latif, Nasir Farooq Butt, Rabia Rathore, Fawad Ahmad Randhawa, Adil Iqbal, Tayyab Latif (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the usage of Remdesivir in COVID 19 patients admitted to Mayo hospital Lahore Methods: This Quasi experimental study was carried out in COVID-19 ward from July 2020 to September 2020 on patients presenting to Mayo Hospital with COVID-19.The sample size (n=150) was calculated through non-probability convenient sampling technique. We gave intravenous Remdesivir to hospitalized COVID-19 patients with proven SARS-CoV-2 infection with an oxygen saturation of ≤94% who were breathing ambient air or needed oxygen support and had an oxygen saturation of less than 94%. Remdesivir was administered to patients over the course of a 10-day course, starting with 200 mg intravenously (I/V) on day 1 and continuing with 100 mg per day for the following nine days. Results: Among 150 participants in our study, 103 (69%) were male and 47(31.3%) were females. Mean age was 57.37±13.42years. Selected parameters were evaluated at day 1, 5 and 10. Significant improvement in fever, dyspnea score, serum C- Reactive proteins (CRP) and lactate dehydrogenase (LDH) was found on day 1 and 10 with a p value of 0.01 to 0.000 for CRP and 0.48 to 0.000 for LDH respectively. Serum ferritin also showed a statistical difference with a significant p value of 0.038 at day 10 as compared to day 1 and 5. Conclusion: Among patients presenting with severe Covid-19, clinical improvement was noticed earlier in those who received Remdesivir than those who didn’t receive this drug. Measurement of effectiveness will require ongoing randomized controlled trials of Remdesivir drug therapy. Keywords: COVID-19, intravenous Remdesivir, earlier clinical improvement, outcome, oxygen support, breathlessness